SISTEM PAKAR NUTRITION PLANUNTUK ORANG DEWASA DENGAN METODE FORWARD CHAINING BERBASIS WEBSITE - Adang Nuryana (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
The problem of nutrition is still a public health problem in Indonesia. Malnutrition has not been resolved, the prevalence of overweight and obesity has begun to increase, especially in the middle and upper socioeconomic groups in urban areas. This is particularly troubling because it threatens the quality of Human Resources (HR) is indispensable in the future (Depkes RI, 2007). Changes in diet and physical activity resulted in the increasing number of people experiencing nutritional problems, such as overweight/obesity and malnutrition. Diet as the main factor nutritional problems, basically can be overcome by regulating the intake of good nutrition for consumption. But unfortunately, not many people know the setting of a good and proper diet. The Nutrition Plan was created as an expert system in determining balanced nutrition for adults based on body mass index and daily diet using forward chaining inference. This system will recommend what foods are suitable for every adult in accordance with the needs of calories per day in the hope of prevalence rates for the Indonesian people suffering from malnutrition and overweight can be reduced significantly. In addition to facilitating the public, especially normal adults to know the nutritional information in order to achieve a healthy lifestyle.